Social Performance of Rural Bank: Impact of Commercialization Factors - Puteri, Hesi Eka (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2020)
Although social performance is an important target in islamic rural bank, this performance is constrained by various factors of commercialization. This study examined the impact of commercialization factors covering profitability, regulation, and competition on the social performance of rural bank. This research was quantitative that based on a survey on fifty units of rural banks in West Sumatera province of Indonesia from 2016 to 2018. The secondary data collected from the publication of financial services authority and other financial documents at rural banks then analyzed with panel data regression. The findings of this research showed that profitability and competition influenced the social performance, meanwhile regulation could not predict the achievement of social performance.Ã‚Â This finding reinforced the previous studies which identified the impact of some commercialization indicators towards the achievement of social performance but there was no regulationÃ¢â‚¬â„¢s impact on social performance.Ã‚Â The impact of regulation which was originally expected to be able to strengthen the social responsibility mission of rural banks evidently did not stimulate the increase of social performance.